Intersection between individual, household, environmental and system level factors in defining risk and resilience for children in Kenya's ASAL: A qualitative study. - Esther Jebor Chongwo; Barack Aoko; Martha Kaniala; Moses Esala; Phillis Magoma; Eunice Njoroge; Susan Nyamanya; Joyce Marangu; Anil Khamis; John Ng'asike; Anja C Huizink; Amina Abubakar (PLoS ONE)
Introduction Children growing up in arid and semi-arid regions of Sub-Saharan Africa (SSA) face heightened risks, often resulting in poor developmental outcomes. In Kenya, the arid and semi-arid lands (ASAL) exhibit the lowest health and developmental indicators among children. Despite these risks, some children grow up successfully and overcome the challenges. However, there is limited comprehensive data on sources of risks and resilience in these children, particularly research that incorporates community perspectives and indigenous knowledge. Systematic documentation of factors influencing child outcomes is crucial for understanding the overall burden, informing policy and implementing targeted interventions. This study aimed at bridging this gap. Methods The study was conducted in 10 ASAL counties in Kenya. Purposive and snowballing techniques were used to recruit 11 key informants per site with varied levels of involvement in early childhood development and primary caregivers. Using a semi-structured interview guide, 103 telephonic interviews were conducted between June and August 2022, involving 68 key informants and 35 caregivers. Thematic approach was used to analyze the data, using NVIVO software. Results The mean age of the participants was 44years (SD = 11 years). The findings, viewed through the lens of Bronfenbrenner's ecological systems theory, reveal a complex interplay of contextual factors impacting children's development. These factors range from individual and biological aspects to family, community, systemic, and environmental level, including climatic challenges. Identified risk factors encompassed issues such as young caregiver's age, low literacy, mental health issues, drug abuse, domestic violence, malnutrition, poverty, lack of paternal involvement, early marriages, female genital mutilation, drought, heat stress, and insecurity. Nonetheless, sources of resilience include breastfeeding, immunization, responsive caregiving, family and community support, higher socio-economic status (SES), cultural practices, self-motivation, hard work, community role models, religious activities and quality service provision. Conclusion Urgent attention is needed to address the multifaceted challenges faced by children in ASAL regions. The study underscores the importance of addressing the root causes of risks while harnessing community strengths and resources to safeguard and promote the holistic development of these children.